Phytohormone profiling in an evolutionary framework - Schmidt, Vojtěch; Skokan, Roman; Depaepe, Thomas; Kurtović, Katarina; Haluška, Samuel; Vosolsobě, Stanislav; Vaculíková, Roberta; Pil, Anthony; Dobrev, Petre Ivanov; Motyka, Václav; Van Der Straeten, Dominique; Petrášek, Jan (Nature communications, 2024)
The genomes of charophyte green algae, close relatives of land plants, typically do not show signs of developmental regulation by phytohormones. However, scattered reports of endogenous phytohormone production in these organisms exist. We performed a comprehensive analysis of multiple phytohormones in Viridiplantae, focusing mainly on charophytes. We show that auxin, salicylic acid, ethylene and tRNA-derived cytokinins including cis-zeatin are found ubiquitously in Viridiplantae. By contrast, land plants but not green algae contain the trans-zeatin type cytokinins as well as auxin and cytokinin conjugates. Charophytes occasionally produce jasmonates and abscisic acid, whereas the latter is detected consistently in land plants. Several phytohormones are excreted into the culture medium, including auxin by charophytes and cytokinins and salicylic acid by Viridiplantae in general. We note that the conservation of phytohormone biosynthesis and signaling pathways known from angiosperms does not match the capacity for phytohormone biosynthesis in Viridiplantae. Our phylogenetically guided analysis of established algal cultures provides an important insight into phytohormone biosynthesis and metabolism across Streptophyta.
Keywords: Cytokinins; oxylipiny; cytokininy; signální transdukce; biologická evoluce; Abscisic Acid; Gene Expression Regulation, Plant; kyseliny indoloctové; kyselina salicylová; kyselina abscisová; Oxylipins; Indoleacetic Acids; Signal Transduction; regulátory růstu rostlin; Cyclopentanes; Biological Evolution; Salicylic Acid; Ethylenes; ethyleny; Viridiplantae; fylogeneze; regulace genové exprese u rostlin; Plant Growth Regulators; cyklopentany; Phylogeny; Chlorophyta